Improved salt tolerance of Synechococcus elongatus PCC 7942 by heterologous synthesis of compatible solute ectoine - Dong, Zhengxin; Sun, Tao; Zhang, Weiwen; Chen, Lei (Frontiers in Microbiology, 2023)
Salt stress is one of the essential abiotic stresses for the survival of cyanobacteria. However, the realization of large-scale cultivation of cyanobacteria is inseparable from the utilization of abundant seawater resources. Therefore, research on the regulatory mechanism, as well as the improvement of salt tolerance of cyanobacteria is fundamental. Ectoine, a compatible solute which was found in halophilic microorganisms, has potentiality to confer salt tolerance. Here in this article, the salt tolerance of Synechococcus elongatus PCC 7942 (Syn7942) was significantly improved via expressing the ectoine biosynthetic pathway, reaching an increased final OD750 by 20% under 300 mM NaCl and 80% under 400 mM NaCl than that of wild-type (WT), respectively. Encouragingly, the engineered strain could even survive under 500 mM NaCl which was lethal to WT. In addition, by introducing the ectoine synthetic pathway into the sucrose-deficient strain, the salt tolerance of the obtained strain Syn7942/Δsps-ect was restored to the level of WT under 300 mM NaCl stress, demonstrating that ectoine could substitute for sucrose to combat against salt stress in Syn7942. In order to study the difference in the regulation of mechanism on the salt adaptation process after replacing sucrose with ectoine, transcriptomic analysis was performed for Syn7942/Δsps-ect and WT. The differentially expressed gene analysis successfully identified 19 up-regulated genes and 39 down-regulated genes in Syn7942/Δsps-ect compared with WT under salt stress condition. The results also showed that the global regulation of Syn7942/Δsps-ect and WT had certain differences in the process of salt adaptation, in which Syn7942/Δsps-ect reduced the demand for the intensity of sulfur metabolism in this process. This study provides a valuable reference for further salt tolerance engineering in cyanobacteria.